Pengaruh Komitmen Organisasional, Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai dalam Program Pembinaan Narapidana pada Lembaga Pemasyarakatan Kelas II.a Ternate - Muhammad M. Marasabessy; Abdul Rahman Jannang; Adnan Rajak (Fakultas Ekonomi, Universitas Muslim Indonesia, 2022)
Regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 35 of 2018 concerning the Revitalization of Correctional Administration is an effort to progressively re-describe the ideal correctional system implementation model and is based on a holistic analysis of the elements that affect the implementation of correctional duties and functions as well as existing objective conditions. That way a more precise formula will be obtained in solving various problems that have been indicated, in the implementation of the work of the correctional system, with measurable and clear change measures. This study aims to obtain empirical evidence of the influence of Organizational Commitment, Motivation and Work Discipline on Employee Performance in the Inmate Development Programa at the Ternate Class IIA Penitentiary. The variables studied are Organizational Commitment, Motivation and Work Discipline. The sample collection method uses the solvin formula. The resulting sample was 60. Questionnaires were distributed to employees of the Ternate Class IIA Penitentiary. The data analysis test uses the Multiple linear regression method using the statistical package for social scientists (SPSS) V22 program as a statistical test tool. The results of hypothesis testing for the variables Organizational Commitment, Motivation and Work Discipline had a significant effect on the Performance of Ternate Class IIA Penitentiary Employees